The human cathelicidin peptide LL-37 inhibits pancreatic cancer growth by suppressing autophagy and reprogramming of the tumor immune microenvironment - Zhang, Zhu; Chen, Wen-Qing; Zhang, Shi-Qing; Bai, Jing-Xuan; Lau, Ching-Lam; Sze, Stephen Cho-Wing; Yung, Ken Kin-Lam; Ko, Joshua Ka-Shun (Frontiers in Pharmacology, 2022)
Pancreatic cancer is amongst the most lethal malignancies, while its poor prognosis could be associated with promotion of autophagy and the tumor immune microenvironment. Studies have confirmed the pro-tumorigenic nature of the cathelicidin family of peptide LL-37 in several types of cancer. However, at higher doses, LL-37 exerts significant cytotoxicity against gastrointestinal cancer cells. In our study, we investigated the anti-tumorigenic potential of LL-37 in pancreatic cancer and the underlying mechanisms. Our results have shown that LL-37 inhibited the growth of pancreatic cancer both in vitro and in vivo. Mechanistic studies have demonstrated that LL-37 induced DNA damage and cell cycle arrest through induction of reactive oxygen species (ROS). Further study indicates that LL-37 suppressed autophagy in pancreatic cancer cells through activation of mTOR signaling, leading to more accumulation of ROS production and induction of mitochondrial dysfunctions. With combined treatment of LL-37 with the mTOR inhibitor rapamycin, LL-37-induced ROS production and cancer cell growth inhibition were attenuated. Subsequent in vivo study has shown that LL-37 downregulated the immunosuppressive myeloid-derived suppressor cells and M2 macrophages while upregulated the anti-cancer effectors CD8+ and CD4+ T cells in the tumor microenvironment. By using an in vitro co-culture system, it was shown that promotion of M2 macrophage polarization would be suppressed by LL-37 with inhibition of autophagy, which possessed significant negative impact on cancer growth. Taken together, our findings implicate that LL-37 could attenuate the development of pancreatic cancer by suppressing autophagy and reprogramming of the tumor immune microenvironment.